Solution-processable end-functionalized tetrathienoacene semiconductors: Synthesis, characterization and organic field effect transistors applications. (October 2017) - Mamillapalli, Narendra Chary; Vegiraju, Sureshraju; Priyanka, Pragya; Lin, Chih-Yu; Luo, Xian-Lun; Tsai, Hsiang-Chi; Hong, Shao-Huan; Ni, Jen-Shyang; Lien, Wei-Chieh; Kwon, Guhyun; Yau, Shueh Lin; Kim, Choongik; et al.
Abstract: A series of dialkylated tetrathienoacene (TTAR )-based solution-processable small molecular organic semiconductors have been synthesized and characterized for organic field effect transistor (OFET) applications. The central dialkylatedTTAR moiety was end-capped with thiophenylvinylthiophene (TVT ), bithiophene (bT ), and thienothiophene (TT ) to afford new π-conjugated p-type active materials, DTVT-TTAR (1 ), DbT-TTAR (2 ), andDTT-TTAR (3 ), respectively. The physical and electrochemical properties and theoretical calculations as well as OFETs performance and thin film morphologies and microstructures of these new solubleTTAR s are systematically studied. Using a solution-shearing method, DTVT-TTAR exhibits p-channel transport with the highest mobility of up to 0.18 cm 2  V −1 s −1 and current ON/OFF ratios of 10 4 -10 6, which is one of the highest hole mobilities for the solution-processedTTAR -based small molecules. Graphical abstract: Highlights: Synthesis and characterization of dialkylated tetrathienoacene derivatives as semiconductors. Various substituents as end groups for solution-processed p-type semiconductors. P-type transport with highest mobility up to 0.18 cm 2  V −1 s −1 . One of the highest mobilities for dialkylated tetratheinoacene derivaties.